Pilot study on the applicability of boron‐doped diamond electrodes for tooth whitening - Virgilia Klär; Victor Palarie; Andreas Burkovski; Matthias Karl; Tanja Grobecker‐Karl (Wiley, 2022)
Abstract Objectives While various approaches are available for tooth whitening, the basic concept employs the use of peroxides in the form of gels, which are applied to tooth surfaces. Previous studies have shown that reactive oxygen species acting as potent disinfectants can be produced using boron‐doped diamond (BDD) electrodes for the electrolysis of water. With these electrodes being applicable, for example, for endodontic treatment, it was the goal of this pilot study to use such electrodes for tooth whitening. Material and Methods Two groups (n = 10) of intact clinical crowns were obtained by horizontally cutting off roots of extracted human teeth. The crowns were either bleached by applying a commercially available agent based on 40% hydrogen peroxide or were immersed in saline undergoing electrolysis with BDD electrodes. Whitening of specimens was judged on standardized photographs by examiners with three different levels of experience. Statistical analysis was based on Gwet's AC2 coefficient with quadratic weights, Shapiro-Wilk tests, and two‐way analysis of variance of aligned rank transformed data (level of significance set at α = .05). Results Levels of reliability ranging from fair to substantial were recorded for single persons while the level of reliability ranged between fair and moderate for groups of raters. The level of experience had no significant effect on the ratings (p = .2500). The bleaching method had a significant effect on ratings (p = .0005) with BDD electrodes showing less effect. Conclusions Bleaching by applying BDD electrodes was possible, but was not as effective as the use of commercially available in‐office whitening gel. A potential explanation may be seen in different concentrations of reactive oxygen species.